Hubungan Gravida, Jarak Kehamilan Dan Status Gizi Dengan Kejadian Hiperemesis Gravidarum Pada Ibu Hamil Trimester I - Meika Risdayanti BR Ginting; Helni Anggraini; Erma Puspita Sari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Hyperemesis gravidarum is excessive nausea and vomiting in pregnant women that is so severe that it interferes with work. This research was conducted at RSIA Amanna Baturaja which aims to determine the relationship of gravida, gestational interval and nutritional status to the incidence of Hyperemesis Gravidarum. The design of this study used a quantitative analytic survey method with a cross sectional approach. The population is all 1st trimester pregnant women who checked their pregnancy at RSIA Amanna Baturaja in 2020, which amounted to 232 respondents. Sampling using random sampling technique, the sample size is 70 respondents. Data analysis using the chi square test with a significance level of = 0.05. The results showed that there was a relationship between primigravida (p-value 0.017), gestational interval (p-value = 0.041), and nutritional status with the incidence of hyperemesis gravidarum (p-value 0.040). This shows that there is a significant relationship between nutritional status and the incidence of hyperemesis gravidarum. The conclusion is that there is a significant relationship between gravida, pregnancy distance and nutritional status with the incidence of Hyperemesis Gravidarum at Amanna Hospital in Baturaja, East Baturaja District, OKU Regency in 2020. The results of this study can be used as a reference to improve the quality of health services for pregnant women to prevent hyperemesis gravidarum.